Crustal and Mantle Structure Beneath the Southern Payenia Volcanic Province Using Gravity and Magnetic Data - Astort, Ana (2019)
The Auca Mahuida volcanic field lies on the southernmost Payenia Volcanic Province, one of the broadest retroarc volcanic plateaux in the southern Central Andes (~38°S). This voluminous basaltic flooding of Quaternary age was originated from a deep asthenospheric source, interpreted as a mantle plume product of changing slab dynamics. The geometry of this source is deduced from magnetotelluric data, but the limited spatial coverage of this array does not allow a detailed resolution of this anomaly. In order to present a detailed geometry of the conductive anomaly and related crustal magmatic bodies, we used multiple data sources. We combined Magnetic and Bouguer anomalies, Curie isotherm depth (T c ), Elastic Thickness (T e ) and Moho depth derived from the Global Earth Magnetic Anomaly Grid (EMAG2) and terrestrial gravity measurements, all together in a holistic geophysical analysis. The magnetic data depict a nearly 200-km-in-diameter circular anomaly that would correspond to a dense body according to the Bouguer anomaly. Geoid data from the Gravity Field Model (EIGEN-6c4) have been filtered in order to isolate deeper mass influences and visualize the asthenospheric upwelling previously described from magnetotelluric data. Moho inversion yields a crustal attenuation at 36- to 32-km depth coinciding with T e below 20-km depth and a shallow T c (≤15-km depth) at the site where Geoid positive undulation was calculated. Finally, surface analysis allowed defining a topographic swell, compatible with the dimensions of the identified magnetic anomaly, where the main rivers deviated, potentially due to a recent base level change.